Hyocholic acid species improve glucose homeostasis through a distinct TGR5 and FXR signaling mechanism - Zheng, Xiaojiao; Chen, Tianlu; Jiang, Runqiu; Zhao, Aihua; Wu, Qing; Kuang, Junliang; Sun, Dongnan; Ren, Zhenxing; Li, Mengci; Zhao, Mingliang; Wang, Shouli; Bao, Yuqian; et al. (Cell metabolism, 2021)
Hyocholic acid (HCA) and its derivatives are found in trace amounts in human blood but constitute approximately 76% of the bile acid (BA) pool in pigs, a species known for its exceptional resistance to type 2 diabetes. Here, we show that BA depletion in pigs suppressed secretion of glucagon-like peptide-1 (GLP-1) and increased blood glucose levels. HCA administration in diabetic mouse models improved serum fasting GLP-1 secretion and glucose homeostasis to a greater extent than tauroursodeoxycholic acid. HCA upregulated GLP-1 production and secretion in enteroendocrine cells via simultaneously activating G-protein-coupled BA receptor, TGR5, and inhibiting farnesoid X receptor (FXR), a unique mechanism that is not found in other BA species. We verified the findings in TGR5 knockout, intestinal FXR activation, and GLP-1 receptor inhibition mouse models. Finally, we confirmed in a clinical cohort, that lower serum concentrations of HCA species were associated with diabetes and closely related to glycemic markers.